(Re)contextualizing the Trauma to Prevent or Treat PTSD-Related Hypermnesia. (May 2021) - Desmedt, Aline
A cardinal feature of Post-traumatic stress-related disorder (PTSD) is a paradoxical memory alteration including both intrusive emotional hypermnesia and declarative/contextual amnesia. Most preclinical, but also numerous clinical, studies focus almost exclusively on the emotional hypermnesia aiming at suppressing this recurrent and highly debilitating symptom either by reducing fear and anxiety or with the ethically questionable idea of a rather radical erasure of traumatic memory. Of very mixed efficacy, often associated with a resurgence of symptoms after a while, these approaches focus on PTSD-related symptom while neglecting the potential cause of this symptom: traumatic amnesia. Two of our preclinical studies have recently demonstrated that treating contextual amnesia durably prevents, and even treats, PTSD-related hypermnesia. Specifically, promoting the contextual memory of the trauma, either by a cognitivo-behavioral, optogenetic or pharmacological approach enhancing a hippocampus-dependent memory processing of the trauma normalizes the fear memory by inducing a long-lasting suppression of the erratic traumatic hypermnesia.